Enhancement of Sensitivity for Retroreflection-Based Biosensor by Controlling Polymer Brush on Janus Particles - Xu, Yangyang; Choi, Sunjoo; Yoo, Tae Hyeon; Lee, Kyung Jin (Macromolecular Chemistry and Physics, 2024)
Among the methods for onsite detection of specific biomolecules, the use of retroreflective Janus particles (RJPs) is a simple and efficient method for biophotonic probes to detect biotarget molecules with spatioselectivity, which can make the RJPs align toward light sources after capturing the target biomolecules, enhancing retroreflection. Because RJP has two distinct regions with different properties, specific reagents can be easily functionalized through chemical reactions between the functional groups and biotarget molecules. The number of functional groups on RJP will be the critical parameter for efficiency of sensing ability. Here, clickable (azide) polymer brush is introduced on surface of RJP via different surface polymerization methods (grafting to and grafting from method). Azide groups allow for the easy modification of dibenzocyclooctyne-linked biomolecules onto silica particles through click chemistry. RJPs are prepared with different quantities of azide functional groups on their surfaces via solvent volatilization method and metal deposition. Using a retroreflective immunosensing system, sensitive detection of target biomolecules is performed.
Keywords: Bio photonics; Functionalized; Janus particles; On-site detection; Polymer brushes; Property; Retro reflection; Retroreflective sensors; Sensing abilities; Simple++; biosensor; colloid; Janus particles; polymer brush; retroreflective sensor